Analysing OpenStreetMap data for topological errors. (2016) - Sehra, Sukhjit Singh; Singh, Jaiteg; Rai, Hardeep Singh
OpenStreetMap is producing huge spatial data contributed by users of different backgrounds and varying level of mapping experiences. Due to this generated map data may be topologically incorrect, which explicitly expresses the spatial relationship between features. To make the map data navigable, it is important that data is free from topological errors. The current work has been conducted to detect topological errors in OpenStreetMap data. OpenStreetMap data of Punjab (India) has been taken as test data for finding topological errors. For cleaning the topological errors, map data has been processed using different algorithms of open source geographic information systems, and it has been concluded that OpenStreetMap data is not free from topological errors and need a thorough preprocessing before being used for navigation purposes.